The level of teacher stress of mathematical discipline in the initial years of fundamental teaching / O nível de estresse do professor da disciplina da matemática nos anos iniciais do ensino fundamental - Sandra Sueli Falcão Carvalho (Universidade Estadual de Alagoas, 2019)
This research deals with the level of stress of the teacher of Mathematics in the initial years of Elementary School, through a psychoanalytic approach, and is based on the interface between Education and Psychoanalysis, specifically the conditioners of stress levels: anxiety and anguish. It aims to identify as indicators of stress level, which will be analyzed in the light of psychoanalysis, mainly from some devices such as, transfer, desire and bond, which were necessary in the way of this investigation, having as basic references Freud, Lacan and others. The research is qualitative and exploratory. The methodology covers a review of the literature and the application of semi-structured questionnaires for teachers and students. The results show that the improvements related to this problem can be acquired by joining the work of Psychoanalysis with Education, because in this way there will be indication of ways to solve the problem of the teachers involved.